Rectangular stepped patch antenna at GSM 900 for energy scavenging - Md. Din, N.; Chakrabarty, C. K.; Devi, K. K. A.; Sadasivam, S. (EMW Publishing, 2012)
This paper presents a novel 377 Ω rectangular stepped patch antenna with partial ground plane at downlink radio frequency range of GSM-900 band. Two steps are incorporated into the patch antenna, and bandwidth expansion was investigated by the currents flowing through the patch antenna. The antenna simulation was carried out in the ADS 2009 environment. The fabricated antenna on FR4 substrate indicates an impedance bandwidth of 32.7% (310 MHz) at 947 MHz centre frequency with return loss of −28.12 dB. The simulated, test and field results of the antenna design are discussed.